Identification of circular RNAs and their alterations involved in developing male Xenopus laevis chronically exposed to atrazine. (June 2018) - Sai, Linlin; Li, Ling; Hu, Chenyang; Qu, Binpeng; Guo, Qiming; Jia, Qiang; Zhang, Yu; Bo, Cunxiang; Li, Xiangxin; Shao, Hua; Ng, Jack C.; Peng, Cheng
Abstract: Atrazine (AZ) is an environmental endocrine disrupting chemical which can affect the development of amphibians. In our past studies, we demonstrated that chronical exposure to 100 μg/L AZ can cause abnormalities in development and related genes expression of gonads in developing male Xenopus laevis ( X. laevis ) tadpoles. Recent studies by others have demonstrated that circular RNAs (circRNAs) are implicated in multiple developmental anomalies. However, whether circRNAs involve in the effects in AZ-exposed X. laevis remains unknown. In this study, over 68575 circRNAs were detected by circRNA sequencing of testis tissues from control groups ( n  = 3) and AZ-treated X. laevis ( n  = 3). Treatment of AZ led to 405 circRNAs differentially expressed including 44 upregulated and 361 downregulated compared with froglets in the control groups. Two upregulated and 6 downregulated circRNAs were further validated by real-time PCR assay which displayed consistent regulation patterns as shown by the transcriptome sequencing results. Two hundreds and eighty two differentially expressed circRNAs played miRNA sponges roles. Kyoto Encyclopedia of Genes and Genomes pathway analysis of miRNA targets showed that AZ-affected circRNAs are mainly involved in 19 pathways. The Wnt signaling pathway and progesterone-mediated oocyte maturation pathway may be two involved signal pathways. This study for the first time provides evidence that AZ can alter circRNAs which play a role in AZ-induced testicular degeneration of developing male X. laevis through regulation of expressions of functional genes in the testes of X. laevis. Highlights: This study for the first time identified 68575 circRNAs in the testis of X. laevis. AZ induced changes in 405 circRNAs (44 upregulated, 361 downregulated). The predicted target mRNAs of circRNAs by AZ involved in 19 pathways. The Wnt and progesterone-mediated oocyte maturation pathways are involved.